1970
DOI: 10.1113/jphysiol.1970.sp009282
|View full text |Cite
|
Sign up to set email alerts
|

The role of hypothalamic temperature in the control of panting in the chicken exposed to heat

Abstract: SUMMARY1. In unanaesthetized chickens, the temperatures of the hypothalamus, colon and skin have been recorded in relation to the onset and cessation of thermally induced panting.2. During control conditions, hypothalamic temperature showed fluctuations associated with arousal and movement. It was lower than colonic temperature by about 0.90 C but this difference generally decreased during exposure to heat.3. When the birds were exposed abruptly to 400 C, or to ambient temperatures increasing gradually from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 27 publications
1
24
1
Order By: Relevance
“…The mean body-to-brain temperature difference found in the normally hydrated fowls in the present study is within the range reported for other birds under similar experimental conditions. However, in contrast with previous studies in the domestic fowl (Richards 1970(Richards , 1971, we observed an increased degree of brain cooling at higher body temperatures. This discrepancy could be due to (a) the gradual acclimation procedure employed in the present study, as compared with the nonacclimated fowls used in the above studies and (b) the use of nonrestrained birds in the present study.…”
Section: Brain Coolingcontrasting
confidence: 86%
See 1 more Smart Citation
“…The mean body-to-brain temperature difference found in the normally hydrated fowls in the present study is within the range reported for other birds under similar experimental conditions. However, in contrast with previous studies in the domestic fowl (Richards 1970(Richards , 1971, we observed an increased degree of brain cooling at higher body temperatures. This discrepancy could be due to (a) the gradual acclimation procedure employed in the present study, as compared with the nonacclimated fowls used in the above studies and (b) the use of nonrestrained birds in the present study.…”
Section: Brain Coolingcontrasting
confidence: 86%
“…It has been found that the brain temperature in birds may fluctuate in association with circadian rhythms, state of arousal, optical stimulation, and postural changes (Saint Paul and Aschoff 1968;Richards 1970Richards , 1971Scott and van Tienhoven 1971 ;Withers and Crowe 1980). In birds, the arterial blood entering the brain appears to be cooled by heat exchange with cool venous blood in the rete ophthalmicum, resulting in a temperature difference of about 1 ~ between body and brain temperature (Kilgore et al 1979).…”
Section: Brain Coolingmentioning
confidence: 95%
“…For some cm ϫ 18 cm ϫ 25.5 chicks, a 50-W tropical fish tank thermostatic heater (Heetmaster, Danner Mfg., Central Islip, NY) maintained the water in the flask at 42ЊC. This value was selected because (a) the average body temperature of adult domestic chickens at rest under thermoneutral conditions is 41.5ЊC (Richards, 1970), and (b) 1-dayold domestic chicks, tested in a linear thermal gradient, prefer a mean temperature of 41.3ЊC (Ogilvie, 1970). The heated flask provided a discrete heat source against which a chick could huddle (see Figure 2b) and warmed the nest.…”
Section: Apparatusmentioning
confidence: 99%
“…The pH activity profile of ȕ-mannanase was determined by measuring the enzyme activity at 42°C (Richards, 1970) in a pH range of 3.5-11.5, using 50 mM of citrate-NaOH buffer (pH 3.5-6.0), sodium phosphate buffer (pH 6.0-8.0), glycine-NaOH buffer (pH 8.0-10.0) and 3-[cyclohexylamino]-1-propanesulfonic acid buffer (CAPS, pH 10.0-11.5).…”
mentioning
confidence: 99%